Formal versus Bounded Norms in the Psychology of Rationality: Toward a Multilevel Analysis of Their Relationship. Issue 3 (June 2019) - Sturm, Thomas
It is often claimed that formal and optimizing norms of the standard conception of rationality and the heuristics of the bounded rationality approach are at odds with one another. This claim, I argue, is an overly complex one. In order to discuss it adequately, I introduce two sets of distinctions: (a) a system of different kinds of relations between conceptions of rationality, namely relations of elimination, compatibility, and complementarity, and (b) three different levels of possible relations between rules of different theories of rationality—the levels of empirical explanation, normative justification, and normative prescription . I argue that formal and bounded rules are compatible and complementary at the levels of explanation and justification, but probably not so at the level of prescription.